Hidden Flexibility of Strychnine. Issue 6 (15th January 2014) - Schmidt, Manuel; Reinscheid, Frauke; Sun, Han; Abromeit, Hans; Scriba, Gerhard K. E.; Sönnichsen, Frank D.; John, Michael; Reinscheid, Uwe M.
Abstract: The prototypic molecule for conformational rigidity, that is, strychnine, exhibits fast conformational exchange on the NMR timescale at room temperature. A comprehensive description of this up‐to‐now‐hidden stereodynamic behavior is presented, which combines experimental and computational data. Abstract : The prototypic molecule for conformational rigidity, that is, strychnine, exhibits fast conformational exchange on the NMR timescale at room temperature. A comprehensive description of this up‐to‐now‐hidden stereodynamic behavior is presented, which combines experimental and computational data.